Developments in diagnostic and surgical techniques in children with sagittal suture craniosynostosis: a systematic review spanning the last 30 years - Julia Hermann; Christa K. Raak; Thomas Ostermann; Wolfram Scharbrodt (Orphanet Journal of Rare Diseases)
Abstract Background Sagittal suture craniosynostosis is the most usual subtype of craniosynostosis which results from premature fusion of the sagittal suture. It leads to an elongated skull shape known as scaphocephaly. This condition necessitates timely surgical intervention to correct cranial deformities and prevent the associated complications. Over the past three decades, the use of advanced diagnostic methods and the refinement of surgical techniques have improved the understanding of this rare disease. Objective To analyse the development of surgical interventions and diagnostic methods in children suffering from sagittal suture craniosynostosis over the last three decades. Methods A comprehensive literature search was conducted in electronic databases Pubmed and online university libraries to identify articles, studies and case reports reporting on surgical interventions and diagnostic procedures for sagittal suture craniosynostosis the period from 1994 to 2024. Clinical studies, case reports, systematic reviews and meta-analyses were assessed and analysed according to inclusion and exclusion criteria. Prisma guidelines for systematic reviews were considered. Results A systematic literature search identified 301, and a hand search identified 12 articles, of which a total of 57 met the inclusion criteria after careful evaluation. The reviewed studies, predominantly originated from the USA and the Netherlands and provided data on diagnostic methods, surgical techniques, patient-specific characteristics, and outcomes for non-syndromic sagittal craniosynostosis. Conclusions The evolutionary change in surgical and diagnostic strategies for sagittal suture craniosynostosis reflects the ongoing efforts of the medical community to achieve optimal outcomes for affected children. The selection of the appropriate technique remains an individualized decision, considering age, severity of craniosynostosis and other patient-specific factors.